(untitled) (Al-Academy, 2021)
Deconstruction is an intellectual stream that emerged as a result of the changes and requirements of the modern era. This stream extended from thought and literature to all arts, and the research included four chapters. Chapter One: From the research, the research problem was identified in the form of a question: Have the ideas and deconstructive concepts represented in the abstract drawings of the artist Shaker Hassan Al Said? The importance and limits of the research were reviewed and the goal of the research was to reveal the applications of ideas and deconstructive concepts in the abstract drawings of the artist Shaker Hassan Al Said, in addition to defining the most important terms contained in it. Chapter Two: Previous studies, Theoretical framework: a. The beginnings of deconstruction and its sayings, b. Deconstruction applications in European art. Chapter Three: The research community, which included (26) works, the research sample which included five works, Research tool and statistical methods. Chapter Fourth: Results, Conclusions, Recommendations and proposals.